University Students’ Entrepreneurial Performance - Eddy Madiono Sutanto; Peter J. Sigiols; Ivando Putih (Journal of Economics, Business, and Accountancy Ventura, 2018)
Low interest of student to entrepreneurship is a pity as the global university entrepreneurial spirit students survey. To improve the students entrepreneurial performance, such factors take part influencing entrepreneurial performance, such as innovativeness, risk taking, proactiveness, competitive aggresiveness, autonomy, and of course entrepreneurial mindset. This research aims to determine the effect of those variables on entrepreneurial performance of college students of management which are A accredited in Malang City, Indonesia. The samples are 374 students from five universities. The analysis technique used is the test of Goodness Fit Model and Path Coefficients test with the help of the program SmartPLS 2.0 and SPSS. The results indicate that the entrepreneurial mindset has significant effect on innovativeness, risk taking, proactiveness, competitive aggresiveness, and autonomy. Moreover, the characteristics of innovativeness, risk taking, proactiveness, competitive aggresiveness, and autonomy have significant effect on the entrepreneurial performance of college students.